Analisis Faktor Risiko Penyakit Low Back Pain Pada Petani Sayur Di Desa Raya Kabupaten Karo - Santy Deasy Siregar; Carla Vioren Ginting; Mika Trines Aulia Rajagukguk; Riky Suherman Simanjuntak; Eka Lolita Eliyanti Pakpahan (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2026)
Low Back Pain (LBP) is one of the most common musculoskeletal disorders experienced by workers, including vegetable farmers in mountainous areas who repeatedly perform strenuous physical activities. Vegetable farmers in Desa Raya, Karo Regency face a high risk of LBP due to hilly working terrain, heavy lifting loads, non-ergonomic working positions, and long working hours. This study aimed to analyze the relationship between individual, ergonomic, and work environment risk factors and the incidence of LBP among vegetable farmers in Desa Raya, Karo Regency. This study used a quantitative approach with an analytical observational design and a cross-sectional approach. The sample consisted of 96 respondents determined using the Lemeshow formula and an accidental sampling technique. Data were collected through questionnaires and analyzed using the Chi-Square test (Continuity Correction/Fisher's Exact Test) at a 95% confidence level. The results showed that of the 96 respondents, 73 (76.0%) reported LBP complaints. Significant associations were found between age (p=0.008) and length of employment (p=0.043) with the incidence of LBP, while sex showed no significant association (p=0.657). Ergonomic risk factors, namely working position (p=0.242), lifting load (p=0.147), and working duration (p=1.000), as well as work environment conditions (p=1.000), showed no statistically significant associations. This study recommends ergonomic interventions and occupational health education for vegetable farmers to reduce the risk of LBP.